Good Practice Guide : Science : Threshold Learning Outcome 4 : Communication. - Colthorpe, Kay; Rowland, Susan; Leach, Joan (Office for Learning and Teaching, 2013)
This good practice guide is the fourth in a series of guides to be developed to address the Science Threshold Learning Outcomes. It focuses on communication in science. It was produced as part of a project that was concerned with Australian higher education standards. The standards were developed as part of a demonstration project funded by the Australian Government in 2010-11 and facilitated by the Australian Learning and Teaching Council. Academic institutions and teachers, professional bodies, accreditation bodies, employers and graduates participated in the development of minimum threshold learning outcomes for the discipline.